Academic Supervision Strategies in Problems Solving Teacher Performance On Language Learning - Indramawan, Anik; Suhartono, Suhartono (Yayasan Indonesia Emerging Literacy Education, 2023)
The purpose of this research is to determine academic supervision strategies in problems solving teacher performance on language learning. The research approach used is qualitative research. The research subjects were madrasah supervisors, madrasah heads, and teachers. The research was carried out on the supervision activities of madrasa supervisors at MI Darussalam Sambiroto Baron Nganjuk. The research results show that problems with teacher performance on language learning include low teacher professionalism due to the mismatch between teachers' academic qualifications and their professional duties. There are teachers whose academic qualifications are non-Madrasah Ibtidaiyah Teacher Education and are forced to become class teachers and teach general subjects. This condition results in less effective learning management and teachers experience difficulties in planning, implementing and assessing of language learning. Efforts to solve teacher performance problems on language learning are carried out by supervision with coaching and mentoring by the MI head or madrasah supervisor. The academic supervision strategies that has been implemented is class visits and regular teacher meetings. Apart from that, MI heads or madrasah supervisors can apply clinical supervision techniques to solve teacher performance problems on language learning.